2008
DOI: 10.4085/1947-380x-3.2.57
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Burnout in Undergraduate Athletic Training Students at One Western US University

Abstract: Objective: Determine if undergraduate athletic training students enrolled in an accredited athletic training education program (ATEP) and participating in clinical assignments experience burnout. Design and Setting: Undergraduate athletic training students enrolled in a clinical education course were surveyed during the fourth and twelfth weeks of a 15 week semester. Participants answered eight demographic/status questions for correlation. Subjects: Fifty-one undergraduate athleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Our study was refuted in comparison to a study by Riter et al, 8 who found that PA did not have a significant effect on students. When placing emphasis on stress level and mood states, Stilger et al 11 suggest that stress levels may vary with certain academic periods throughout the year.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Our study was refuted in comparison to a study by Riter et al, 8 who found that PA did not have a significant effect on students. When placing emphasis on stress level and mood states, Stilger et al 11 suggest that stress levels may vary with certain academic periods throughout the year.…”
Section: Discussionmentioning
confidence: 64%
“…Stress levels are higher in undergraduate athletic training students who are seniors preparing and making plans following graduation compared to freshmen, who still have time before they need to be concerned with the next step in life. 8 During an academic semester, stress may arise and mood states may vary. Mood state components include depression, anxiety, and anger 9 in individuals and can result from academic workload, clinical experience, and clinical research, for example.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three groups of authors 42,46,68 assessed burnout in ATSs, whereas 3 other groups 36,42,52 explored either perceived frustration or coping strategies. Upper-level students have reported significantly higher burnout scores than lowerlevel students, and most students experienced some level of burnout.…”
Section: Burnout In Atssmentioning
confidence: 99%
“…4 Only recently has socialization into the athletic training profession gained attention. 3,[5][6][7][8][9][10][11][12][13][14][15][16][17] Issues surrounding career choice, 5 educational preparation, 13 student retention, 14 burnout, 15,17 and role strain 16 are among the most recent topics related to the socialization of athletic training students and current professionals. Findings in these areas are contributing to a greater understanding of how and why people choose to become ATs and the various obstacles students and professionals must overcome.…”
mentioning
confidence: 99%